STRATEGI MARKETING PUBLIC RELATIONS DALAM MEMBANGUN BRAND IMAGE DI KC BANK BTN PEKANBARU (Studi Kasus: KPR BTN Platinum) - Tiffani Kumala; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The implementation of the method carried out by public relations greatly affects the satisfaction or comfort of customers towards the Pekanbaru BTN image. Based on the problems in the research, the problem can be formulated in this study, namely how is the marketing public relations strategy in building a brand image on Bank BTN KC Pekanbaru (case study: KPR BTN Platinum)?. The research method used is descriptive qualitative research method. This research was conducted at the Bank BTN TC Pekanbaru located on Jl. Jendral Sudirman No. 393. The schedule of this study is conducted from November 2017 to July 2018. The research subjects are based on a focus on searching data and evidence in fact, can be in the form of interview data, reactions, and responses or information. This research information is from BTN KC Bank Pekanbaru is: Manager 1 Person, Assistant Manager 1 Person, Head of HRD KC BTN Bank Pekanbaru 1 Person and Customer 8 People. The number of speakers was 11 people. The subject taking technique in this study is the Purposive technique. After the data is collected, the researcher analyzes the data using qualitative descriptive analysis. The results of the research can be suggested that the Public Relations Marketing Strategy through Information in building imagedi brand KC Bank BTN Pekanbaru is done by providing information through the media in the form of facebook, instragram, distributing the form of brochures or pamphlets installation. The Public Relations Marketing Strategy through public services in building a brand image on Pekanbaru Bank BTN KC is done by providing good service and being friendly. Public Relations Marketing Strategy through publications in building the imaginary brand Pekanbaru KC Bank BTN is carried out by intensifying promotions in print and social media, promoting special promos related to products and services offered by the Bank to attract customers, improve service and services by doing sales call to customers so that there is a harmonious relationship and reciprocal communication between customer desires and bank services.